RESONANCES OF TOLSTOY’S THOUGHTS IN BRAZILIAN LITERARY JOURNALISM (1909-1922) - Azevedo Neto, Joachin; Queiroz, Mylena Lima (Revista de Literatura, História e Memória, 2017)
The present work aims to discuss the resonance of the thought of the Russian writer Leon Tolstoy (1828-1910) among the intellectuals who collaborated with Brazilian literary journalism, especially the Rio newspaper A Careta. Count Tolstoy, in several of his libels, began to attack the authoritarianism of Russian autocracy, the social contradictions that accompanied modernity, and claim for the redistribution of land in his country. In the Belle Époque tropical, Brazilian writers had to reflect on a similar context. In these terms, we propose an analysis of the resonances of Tolstoism - which advocates the valorization and mystical communion with marginalized social subjects - in the national journalistic and fictional prose such as these are found in texts by José Veríssimo (1857-1916), Fábio Luz (1864-1931 ), Curvelo de Mendonça (1870-1914) and Lima Barreto (1881-1922).